Synthesis of new amino derivatives of 9-(methyl-thio)thieno[3,2-d]pyrimidine and azide-tetrazole equilibrium - E. K. Hakobyan (ՀՀ ԳԱԱ հրատ.)
Starting from the 7-chloro derivative of thieno[3,2-d]pyrimidine 1 a series of new amino derivatives of cyclopenta[4',5'] pyrido[3',2':4,5]thieno[3,2-d] pyrimidine 2 were synthesized.Աշխատանքում նկարագրված է ցիկլոպենտա[4',5']պիրիդո[3',2':4,5] թիենո[3,2-d]պիրիմիդինի նոր ամինոածանցյալների սինթեզը համապատասխան 7-քլորոթիենո[3,2-d] պիրիմիդինի հիման վրա: В работе описан синтез новых 7-аминопроизводных циклопента[4',5']пиридо-[3',2':4,5] тиено[3,2-d]пиримидина на основе соответствующего 7-хлортиено[3,2-d] пиримидина.
Keywords: Organic Chemistry